CURRICULUM CONCEPT MODEL: HUMANISTIC CURRICULUM MODEL - NUR IMAN (CV. Adiba Aisha Amira, 2024)
The Humanistic Curriculum provides solutions for educating students to find their own identity. With the Humanistic curriculum, students are taught to show their potential human nature as individuals that is not touched by other curricula. A person is judged by his character and actions. If the attitude and characteristics are good then it is said that someone has a good personality, and vice versa. However, a person's personality can change anytime and anywhere. Because personality is formed partly due to environmental factors. A person's personality can be seen and felt throughout their life. Therefore, the human personality is said to be a unity in the human soul and body. Learning does not have to be defined as subjects that must be covered, but something that is more meaningful for life, taught in ways that are demonstrative and relevant for students. The Humanistic Curriculum offers other options in relation to subject matter and personality formation.